A high-rate and long cycling life cathode for rechargeable lithium-ion batteries: hollow LiNi0.5Mn0.5O2 nano/micro hierarchical microspheres. (10th February 2016) - Li, Jili; Wan, Lin; Cao, Chuanbao
Abstract: A rechargeable lithium-ion batteries cathode LiNi0.5 Mn0.5 O2 with hollow nano/micro hierarchical microspheres (LNMO-HS) is prepared. LNMO-HS with diameters of about 1 μm is composed of approximately 100 nm primary nanoparticles. The initial discharge capacity of LNMO-HS cathode is as high as 181.5 mAh g −1 at 1 C between 2.5 and 4.5 V. The corresponding capacity retention is 96.3% during 100 charge and discharge cycles. The reversible discharge capacities are 152.2 (10 C) and 134.6 mAh g −1 (15 C), respectively. After 1000 cycles at 15 C, the capacity retention of LNMO-HS cathode is up to 95.5%. The superior rate capability and cyclability of LNMO-HS cathode can be attributed to the distinctive hollow nano/micro hierarchical microspherical structures. It could not only effectively reduce the paths of Li ions diffusion, increase contact area between electrodes and electrolyte but also buffer the volume changes during Li ions intercalation/deintercalation processes.